2020
DOI: 10.1182/blood.2019002792
|View full text |Cite
|
Sign up to set email alerts
|

Increased mTOR activation in idiopathic multicentric Castleman disease

Abstract: Idiopathic multicentric Castleman disease (iMCD) is a rare and poorly understood hematologic disorder characterized by lymphadenopathy, systemic inflammation, cytopenias, and life-threatening multiorgan dysfunction. Interleukin-6 (IL-6) inhibition effectively treats approximately one-third of patients. Limited options exist for nonresponders, because the etiology, dysregulated cell types, and signaling pathways are unknown. We previously reported 3 anti-IL-6 nonresponders with increased mTOR activation who res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…Recently, IL-6 stimulation augmented mTOR activation in idiopathic multicentric Castleman disease (iMCD) patients was reported, furthermore, the degree of mTOR activation in iMCD was comparable to ALPS. This finding supports inhibition of mTOR activation as a novel therapeutic target for iMCD, and is currently under investigation in a clinical study (NCT03933904) ( 126 ).…”
Section: Applications In Non-malignant Hemopathiessupporting
confidence: 64%
“…Recently, IL-6 stimulation augmented mTOR activation in idiopathic multicentric Castleman disease (iMCD) patients was reported, furthermore, the degree of mTOR activation in iMCD was comparable to ALPS. This finding supports inhibition of mTOR activation as a novel therapeutic target for iMCD, and is currently under investigation in a clinical study (NCT03933904) ( 126 ).…”
Section: Applications In Non-malignant Hemopathiessupporting
confidence: 64%
“…Patients with idiopathic multicentric Castleman’s disease who have progressive organ dysfunction and who do not have a response to anti–interleukin-6 therapy are often treated with combination cytotoxic chemotherapy to nonspecifically eliminate hyperinflammatory cells. 81 Other elevated serum cytokines and cellular signaling pathways that could be considered for therapeutic targeting include CXCL13, CXCL10 (interferon-inducible protein 10 [IP-10]), VEGF-A, 82 type I interferon, 83 mTOR complex 1 (mTORC1), 84 and JAK-STAT3. These findings have led to treatment with the mTORC1 inhibitor sirolimus in patients with idiopathic multicentric Castleman’s disease who do not have a response to anti–interleukin-6 therapy.…”
Section: Monogenic or Autoimmune Cytokine Stormmentioning
confidence: 99%
“…Furthermore, data extracted into ACCELERATE have served as critical correlative data for translational research performed on biospecimens around the world; patient data and tissue biospecimens collected from ACCELERATE have been used in published and ongoing translational and clinical studies that have led to treatment guidelines, critical biological insights, and the discovery of therapeutic targets ( Figure 6 ). 14 , 15 , 16 , 17 , 18 , 19 Overall, ACCELERATE patient data and tissue samples have enabled translational research studies that shed light on iMCD pathogenesis and will serve as an engine for future discovery.…”
Section: Resultsmentioning
confidence: 99%
“…In the past 3 years, data and tissue samples collected for ACCELERATE have been used in 5 published studies that have identified key cell types, signaling pathways, chemokines, therapeutic targets, and optimal treatment approaches. 14 , 15 , 16 , 17 , 19 The ACCELERATE model may also be helpful for other rare disease research studies.…”
Section: Discussionmentioning
confidence: 99%